Distortion costs and effects of price liberalisation in Russian energy markets: A CGE analysis - Leena Kerkelä (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
Russia s economy is energy intense and wasteful of resources.This situation has arisen in part due to the country s ample energy supplies and regulated privileges for domestic consumers.Recently enacted and proposed reforms intended to increase the efficiency of the energy sector by raising domestic energy prices also have implications for the export levels of Russian energy commodities. In this study, we estimate the costs of the subsidised energy system in an allocative sense and then analyse recent moves of the Duma to boost gas and electricity prices to bring them into line with market-based pricing.Our analysis uses a multi-region general equilibrium model (GTAP) modified to express the global dimensions of the subsidisation policy and suggested reforms.Preliminary results show that current subsidies extract over 6% of GDP and limit the potential benefits of Russia s comparative advantage in energy commodities.Increases of 6% in electricity and 10% in the price of regulated gas improve efficiency by reducing distorting subsidies and distinctly shifting output from domestic markets to exports.
URN:NBN:fi:bof-201408071974
Keywords: D58; F17; H71; Q43; Q48; 330; CGE modelling; energy market liberalisation; Russia